Union and Empire: The making of the United Kingdom in 1707 - Macinnes, Allan I (Cambridge University, 2013)
Macinnes, a leading authority on 17th century Scotland, offers a major new interpretation of the 1707 Act of Union and the making of the United Kingdom. The book will appeal to scholars and students of Scottish history, early modern British and European history and imperial history